Clonal expansion and horizontal transmission of epidemic F2:A1:B1 plasmids involved in co-spread of rmtB with qepA and blaCTX-M-27 in extensively drug-resistant Salmonella enterica serovar Indiana isolates. (15th November 2018) - Fang, Liang-Xing; Deng, Guo-Hui; Jiang, Qi; Cen, Dao-Ji; Yang, Run-Shi; Feng, Yun-Yun; Xia, Jing; Sun, Jian; Liu, Ya-Hong; Zhang, Qijing; Liao, Xiao-Ping
Abstract: Objectives: To investigate the prevalence and transmission of 16S rRNA methylase genes among Salmonella isolates from food animals in China. Methods: A total of 310 Salmonella isolates collected from food animals in seven provinces of China during 2016–17 were screened for 16S RMTase genes. The clonal relationship of the 16S RMTase-producing isolates and their plasmid contents were also characterized. Results: rmtB and armA were respectively identified in 12 and 1 Salmonella enterica serovar Indiana ( Salmonella Indiana) isolates from farmed ducks. These 13 isolates concurrently expressed high-level resistance to amikacin, cefotaxime and ciprofloxacin. They were assigned to seven distinct PFGE patterns and the high similarity among 10 of the 12 rmtB -carrying isolates suggests clonal expansion. The rmtB gene was co-transferred with bla CTX-M-27 - qepA and qepA in eight and two of the isolates, respectively, and was located on F2:A1:B1 plasmids with sizes of 135 and 100 kb, respectively. These 10 rmtB- bearing plasmids showed four restriction patterns with a high similarity. Four representative rmtB -bearing plasmids were fully sequenced and they exhibited remarkable similarity and possessed typical FII backbones. The primary differences were located in the region between bla TEM-1 and ycgA . Furthermore, a novel MDR region (13.5 kb) was identified that contained qepA, rmtB and bla CTX-M-27 . Conclusions: This is the first report, to our knowledge, of the prevalence and complete sequences of plasmids simultaneously containing rmtB, qepA and bla CTX-M-27 . These findings underscore a major public health threat posed by epidemic F2:A1:B1 plasmids bearing qepA - rmtB - bla CTX-M-27 that are circulating in XDR Salmonella Indiana clonal isolates from waterfowl husbandry.